STRATEGI PGN AREA SEMARANG DALAM MENJANGKAU GENERASI BABY BOOMERS DAN X - Nor Kayatun; Naiza Rosalia (KAGANGA KOMUNIKA: Journal of Communication Science, 2026)
The rapid advancement of digital technology has encouraged businesses to implement digital marketing strategies, yet differences in digital literacy across generations pose a particular challenge, especially among Baby Boomer and Generation X customers. This study aims to examine the marketing communication strategy of PGN Area Semarang in supporting digital marketing for both generations. This research employs a descriptive qualitative approach with data collected through in-depth interviews, observation, and documentation involving two internal informants and five customers from the Baby Boomer and Generation X cohorts. The findings reveal that PGN Area Semarang has comprehensively adopted an Integrated Marketing Communication (IMC) approach by combining elements of advertising, sales promotion, public relations, personal selling, and direct marketing, while implementing digital marketing through various channels such as WhatsApp ChatBot, WhatsApp Customer Management, Pertamina 135, the PGN Mobile application, and social media platforms. A notable finding of this study is the involvement of partner technical teams who went beyond their operational roles by actively educating customers on digital service usage, making them an organic form of educational communication in supporting digital marketing adoption. This study concludes that the success of digital marketing is not solely determined by the availability of technology, but also by the company's ability to flexibly integrate digital and conventional communication based on customer characteristics.   Keywords: Marketing Communication Strategy, Digital Marketing, Integrated Marketing Communication, Baby Boomers, Generation X